Implementasi Penggunaan Sistem Pelacakan Menggunakan Antena Tracking Sistem - Ahmad Fauzan (Pusat Riset dan Inovasi Nasional, 2022)
Satellites are objects in space that move around the earth according to certain orbits. Satellite communication systems can be regarded as a communication system using satellites as repeaters. Satellite communication systems can be regarded as a communication system using satellites as repeaters. The satellite functions as an active repeater where the process of amplifying signal power and frequency translation occurs on the satellite. The satellite is a repeater whose function is to amplify the signal from the earth station and retransmit it on a different frequency to the receiving earth station. The path on each channel from the receiving antenna to the transmitting antenna on the satellite is called the satellite transponder. In addition to amplifying the signal, the transponder also functions as isolation from other RF (Radio Frequency) channels.